2021
DOI: 10.1039/d1tb01974k
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing superhydrophobic coatings for enhancing the surface corrosion resistance of magnesium alloys

Abstract: A superhydrophobic Mg alloy was obtained by depositing SiO2-F NPs in the presence of PDA, presenting excellent capability against corrosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…After modification with SA, an SHPS with a θ c of about 167.7 ± 0.05° was obtained. Gu et al (2021) prepared a rough polydopamine layer on Mg alloy by dipping it in a dopamine solution. Then the SHPS ( θ c ∼ 152°) was created by immersing the sample into a solution containing hydrophobic nano-SiO 2 particles.…”
Section: Superhydrophobic Surfaces On Mg Alloymentioning
confidence: 99%
“…After modification with SA, an SHPS with a θ c of about 167.7 ± 0.05° was obtained. Gu et al (2021) prepared a rough polydopamine layer on Mg alloy by dipping it in a dopamine solution. Then the SHPS ( θ c ∼ 152°) was created by immersing the sample into a solution containing hydrophobic nano-SiO 2 particles.…”
Section: Superhydrophobic Surfaces On Mg Alloymentioning
confidence: 99%
“…[107,108] SiO 2 -F NPs dispersed uniformly in PDA coating may form a stable superhydrophobic surface with a WCA of 155°and thereby prevent the infiltration of inorganic ions such as Cl − , thus decreasing the corrosion current by an order of magnitude (8.084 × 10 −6 A cm −2 ) compared with undoped coated samples (1.218 × 10 −5 A cm −2 ). [109] Third, impregnating NPs that have small particle sizes (such as nBG, ZnO NPs, and Ce-HA NPs) [26,97,104] on the surface of organic fibers may increase fiber diameter, improve surface chemistry, and reduce fiber gaps, thereby impeding the deposition and penetration of corrosive ions. For example, nBG increased the diameter of PCL nanofibers used to coat an AZ91 Mg alloy surface and thereby enhanced the interception of corrosive products and ions.…”
Section: Improving Corrosion Resistance To Control the Degradation Ra...mentioning
confidence: 99%
“…In addition, air bubbles generated from corrosive actions can cause local alkalinity in the in vivo environment, limiting their clinical application. Several studies have shown that the preparation of a superhydrophobic surface on the surface of magnesium alloy can form a thin air layer between the liquid and the metal to reduce the contact area between the corrosive liquid and the surface of magnesium alloy. The formation and presence of the thin layer can effectively prevent the corrosion of the substrate by body fluids and prolong the service life. Therefore, preparing superhydrophobic surfaces on the surface of medical magnesium alloys has become a critical research field in recent times.…”
Section: Introductionmentioning
confidence: 99%